2012
DOI: 10.4103/0378-6323.93632
|View full text |Cite
|
Sign up to set email alerts
|

Ultrathin split-thickness skin grafting followed by narrowband UVB therapy for stable vitiligo: An effective and cosmetically satisfying treatment option

Abstract: Ultrathin split-thickness skin grafting, when combined with NBUVB therapy, leads to better cosmetic outcome with faster onset of repigmentation in resistant stable vitiligo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 17 publications
2
27
1
Order By: Relevance
“…Overlapping of graft edges at the recipient site can prevent this complication. [78] In contrast to the above mentioned “perigraft halo,” the halo, which we found in our patient, was around the individual grafts. A possible reason for this could be circular scarring that occurred between the graft and the normal skin.…”
Section: Discussioncontrasting
confidence: 84%
See 1 more Smart Citation
“…Overlapping of graft edges at the recipient site can prevent this complication. [78] In contrast to the above mentioned “perigraft halo,” the halo, which we found in our patient, was around the individual grafts. A possible reason for this could be circular scarring that occurred between the graft and the normal skin.…”
Section: Discussioncontrasting
confidence: 84%
“…[178] Two factors could be responsible for this perigraft halo in punch grafting. First, improper placement of donor grafts, that is, far from the margin of the patch so that the repigmentation does not extend till the margin.…”
Section: Discussionmentioning
confidence: 99%
“…There was no graft rejection in any of the patients. Imran mazid et al, (11) observed repigmentation is greater in patients treated with photo chemotherapy plus ultra thin epidermal skin graft versus punch grafts alone.…”
Section: Discussionmentioning
confidence: 99%
“…Points that need to be kept in mind to minimize these complications and to improve the cosmetic results are:[252729]…”
Section: Miniature Punch Graftingmentioning
confidence: 99%
“…The procedure has been termed as ‘ultra-thin skin grafting’ in some clinical studies. [2829] The procedure differs from a traditional split-thickness skin grafting in that the graft that is used is totally translucent, without any whitish tissue on the undersurface. Another difference is that the graft in case of ultra-thin skin grafting usually falls off within 10–14 days.…”
Section: Miniature Punch Graftingmentioning
confidence: 99%